Screening and validation of a novel T stage-lymph node ratio classification for operable colon cancer. - Pei, Jun-Peng; Zhang, Rui; Zhang, Nan-Nan; Zeng, Yong-Ji; Sun, Zhe; Ma, Si-Ping; Zhou, Jian-Guo; Li, Xin-Xiang; Fan, Jin; Zhu, Ji; Abe, Masanobu; Mei, Zu-Bing; et al. (Annals of Translational Medicine, 2021)
Background: Lymph node ratio (LNR) has advantages in predicting prognosis compared with American Joint Committee on Cancer (AJCC) pathological N stage. However, the prognostic value of a novel T stage-lymph node ratio (TLNR) classification for colon cancer combining LNR and pathological primary tumor stage (T stage) is currently unknown. Methods: We included 62,294 patients with stage I-III colon cancer from the Surveillance, Epidemiology, and End Results Program as a training cohort. External validation was performed in 3,327 additional patients. A novel LNR stage was established and combined with T stage in a novel TLNR classification. Patients with similar survival were grouped according to T and LNR stages, with T1LNR1 as a reference. Results: We developed a novel TLNR classification as follows: stages I (T1LNR1-2, T1LNR4), IIA (T1LNR3, T2LNR1-2, T3LNR1), IIB (T1LNR5, T2LNR3-4, T3LNR2, T4aLNR1), IIC (T2LNR5, T3LNR3-4, T4aLNR2, T4bLNR1), IIIA (T3LNR5, T4aLNR3-4, T4bLNR2), IIIB (T4aLNR5, T4bLNR3-4), and IIIC (T4bLNR5). In the training cohort, the novel TLNR classification had better prognostic discrimination (area under receiver operating characteristic curve, 0.621 vs. 0.608, two-sided P<0.001), superior model-fitting ability for predicting overall survival (Akaike information criteria, 561,129 vs. 562,052), and better net benefits compared with the AJCC 8th tumor/node/metastasis classification. Similar results were found in the validation cohort for predicting both overall and disease-free survival. Conclusions: This novel TLNR classification may provide better prognostic discrimination, model-fitting ability, and net benefits than the AJCC 8th TNM classification, for potentially better stratification of patients with operable stage I-III colon cancer; however, further studies are required to validate the novel TLNR classification.
EVALuna2:490993